On the estimation of precipitation rate by a new method of analysis of meteorological radar echoes(2) (abstract) - Hoshiyama,Mitsuo; Hatanaka,Masahiko; Nishitsuji ,Akira; Wada, Makoto (National Institute of Polar Research, 1993)
P(論文) At Syowa Station, microwave radar echo data from clouds and precipitation have been accumulated. We have studied how to estimate precipitation rate using observed radar echoes. In this abstract, we report how to evaluate some physical characteristics of precipitation particles, which are important to analyze radar echoes. (1) Temperature of precipitation particles at each altitude : We are able to use temperature data at each altitude, obtained by radiosonde at Syowa Station. But the temperature is usually different from that of precipitation particles. In case of dense particles falling at high speed, this difference tends to increase. In the opposite case, it is considered that particle and air temperatures are equal. In the latter case, characteristics of a precipitation particle are determined by temperature around the particle. (2) Water volume content of precipitation particles : There is an empirical relation between water volume content of snow-flakes (Pw) and particle density ( departmental bulletin paper